Low‐cost tools mitigate climate change during reproduction in an endangered marine ectotherm. Issue 7 (6th April 2021) - Clarke, Leo J.; Elliot, Rebecca L.; Abella‐Perez, Elena; Jenkins, Stuart R.; Marco, Adolfo; Martins, Samir; Hawkes, Lucy A.
Abstract: The impacts of anthropogenic climate change will be most dramatic for species that live in narrow thermal niches, such as reptiles. Given the imminent threat to biodiversity, and that actions to reduce carbon emissions are not yet sufficient, it is important that a sound evidence base of potential mitigation options is available for conservation managers. Successful incubation and production of male sea turtle hatchlings is threatened by increased global temperatures (sex is determined by the temperature at which eggs incubate). Here we test two conservation tools to reduce incubation temperatures: clutch splitting and clutch shading, on a nesting loggerhead turtle Caretta caretta population in the Eastern Atlantic Ocean. During the thermosensitive period of incubation, split and shaded clutches were both 1.00°C cooler than control nests. Clutch splitting (mean: 45 eggs) reduced nest temperatures by reducing metabolic heating during incubation compared to controls (mean: 92 eggs). Modelled primary sex ratios differed between nest treatments, with 1.50% (±6% SE ) females produced in shaded nests, 45.00% (±7% SE ) females in split nests and 69.00% (±6% SE ) females in controls. Neither treatment affected hatchling size, success, mass or vigour. When clutch splitting was repeated 2 years later, hatch success was higher in split clutches compared to controls. Synthesis and applications . Clutch splitting and clutch shading successfully altered the thermal profile of incubating turtle nests. When there is sufficient knowledge to better understand the effects of intervention on fundamental population demographics, they will be useful for reducing incubation temperatures in sea turtle nests, potentially increasing nest survival and male hatchling production. The effect of clutch splitting in reducing nest temperature was lower relative to clutch shading, but requires significantly less funding, materials and specialist skill, key factors for management of turtle rookeries that are often in remote, resource‐limited areas. Abstract : Clutch splitting and clutch shading successfully altered the thermal profile of incubating turtle nests. When there is sufficient knowledge to better understand the effects of intervention on fundamental population demographics, they will be useful for reducing incubation temperatures in sea turtle nests, potentially increasing nest survival and male hatchling production. The effect of clutch splitting in reducing nest temperature was lower relative to clutch shading, but requires significantly less funding, materials and specialist skill, key factors for management of turtle rookeries that are often in remote, resource‐limited areas.